FORMULATION AND EVALUATION OF NIOSOMAL SUSPENSION OF CEFIXIME - Kumar, Bhama Santhosh; Krishna, Rakhi; Ps, Lakshmi; Vasudev, Deepa T; Nair, Sreeja C (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives : The present study was aimed to overcome the problems associated with the drug such as bioavailability, to reduce the dosage regimen, half life and to determine the appropriateness of niosomal formulation as a drug carrier. Methods: The niosomal suspension was prepared by thin film technique, by varying ratios of span 60 and cholesterol and varying the concentration of span 60. The prepared four formulations were evaluated for various parameters. Results: The optimized formulation had a vesicular size of 250-400nm .Varying the concentration of span 60 ,the entrapment efficiency demonstrated that it had a considerable task.The highest entrapment efficiency was 95.3%. The kinetics study confirmed that the liberation of drug from the niosomal suspension is in a restricted manner. The statistical optimization showed that NS2 is the optimized formulation. The gastrointestinal enzymes showed no significant change in the release of drug from the formulation. The Zone of Inhibition showed that Optimized formulation has better activity than the marketed formulation. The MIC was found to be 0.05mg , hence can be used as a efficient carrier for delivery of Cefixime. Conclusion: The present study concludes that the prepared Niosomal suspension is a convenient and efficiency carrier for the delivery of antibacterial drug. Besides this, it provided controlled delivery of drug.